KECEPATAN ADUK DAN WAKTU KONTAK OPTIMUM PEMBUATAN BIODIESEL DARI MINYAK JELANTAH - Dwi Kartika; Eva Vaulina; Senny Widyaningsih; Moch. Chasani (Molekul, 2010)
Synthesis of biodiesel from waste cooking oil using activated natural zeolite catalyst has been done. Activation of the natural zeolite was done by refluxing with HCl 6M for 30 min, calcining and oxydizing at 500°C for 2 hours, consecutively. The variation of stirring speed were 350, 700, 1100 and 1200 rpm. The variation of reaction time were varied from 15, 30, 45, 60, and 120 min. The conversion of biodiesel was determined by 1H NMR spectrometer. The results showed that the optimum condition of biodiesel synthesis using esterification process were reached at 700 rpm and 15 minutes, which gave biodiesel conversion of 100%.